Exploring alternate methods for predicting sorption-desorption parameters for environmental phosphorus loss assessment in poultry litter impacted soils. (1st September 2022) - Chakraborty, Debolina; Prasad, Rishi; Watts, Dexter B.; Torbert, H. Allen
Abstract: Repeated applications of poultry litter (PL) in weathered soils cause soil phosphorus (P) accumulation and is a major environmental concern. Much remains unknown about the distribution of inorganic P (Pi ) and organic P (Po ) forms along with their retention and release characteristics in soils that have had a history of PL application. The objectives of this study were to 1) determine P loss risk by investigating the distribution of Pi and Po forms, P sorption-desorption parameters, and soil P saturation ratio (PSR; molar ratio of P/[Al + Fe]); and 2) predict the P sorption-desorption parameters using selected soil variables or soil test indicator, PSR. Forty soil samples from 10 random locations within seven pasture fields located in Piedmont soil region were selected and separated into four depths: 0–5, 5–15, 15–30, and 30–45 cm. These fields received annual PL applications ranging from 26 to 92 kg P ha -1 for the past 10 years. The P forms were determined using sequential P fractionation. Soil P retention characteristics were determined using Langmuir isotherm. Soil PSR was determined using oxalate extract (PSROx ). Surface 0–5 cm soils had significantly higher concentrations of labile Pi, intermediately available Pi, organic P pools, higher equilibrium P concentration (EPC), and PSROx compared to the lower depths, which indicated saturation of the P sorption sites from repeated PL application. Regression analyses used to predict P sorption-desorption parameters from soil test variables suggest inclusion of multiple soil variables, which may be time-consuming and not always feasible. The strong relationship between P sorption-desorption parameters and PSROx indicates that PSROx can be effectively used to predict P sorption-desorption parameters for the Piedmont soils without performing time-consuming batch isotherm experiments. Further studies would be needed to validate the relationship for other soil types under different environmental conditions. Graphical abstract: Image 1 Highlights: P fractionation in poultry litter impacted soils identified intermediately available Pi as the dominant pool in 0–5 cm soils. Surface soils had lower P sorption capacity and higher desorption potential compared to the soils in lower depths. P saturation ratio (PSR) was strongly related to P sorption-desorption parameters. PSR can be effectively used to predict P sorption-desorption parameters for Piedmont soil region.